M-learning w nauce języków obcych – potencjał i ograniczenia - Jaworska, Mariola (Neofilolog, 2024)
M-learning refers to learning supported by mobile devices such as smartphones or tablets, which can be taken anywhere and utilized independently of place and time. The continuous improvement of portable devices gives them new features, among which solutions favoring the development of language competencies can play an important role. The first part of the article will discuss theoretical justifications and models related to mobile learning, as well as associated approaches such as multimedia learning and multimodality. In the second part, with reference to available results of empirical research, an attempt will be made to indicate the potential and the limitations of mobile learning, as well as to signal research directions encompassing issues in this area that are worth exploring in the future.